Bleeding risk and selective serotonin reuptake inhibitors treatment after percutaneous coronary intervention: a propensity-matched study. (14th October 2021) - Gonzalez-Manzanares, R; Ruiz-Moreno, M; Carmona-Artime, L; Rodriguez-Nieto, J; Piserra, A; Perea-Armijo, J; Flores, G; Fernandez-Ruiz, A; Ojeda, S; Hidalgo, F J; Suarez De Lezo, J; Mazuelos, F; et al.
Abstract: Background: Cardiovascular disease and mental disorders frequently coexist. Selective serotonin reuptake inhibitors (SSRIs) are often used to treat depressive and anxiety disorders but have been associated with an increased risk of bleeding due to platelet dysfunction. Up to 10% of patients with coronary artery disease are concomitantly treated with dual antiplatelet therapy (DAPT) and SSRI. Previous studies have assessed the risk of bleeding in patients treated with SSRI and clopidogrel-based DAPT, with contradictory results. However, there is no data regarding the use of SSRI and potent P2Y12 inhibitors (ticagrelor, prasugrel) or triple antithrombotic therapy (TAT). Purpose: To evaluate the bleeding outcomes in a real-world population of patients undergoing percutaneous coronary intervention (PCI) treated with SSRI and DAPT or TAT after a year follow-up. Methods: We conducted a retrospective study including all patients undergoing PCI at a high-volume center during 2018. Patients taking SSRI were propensity-score-matched (PSM) 1:1 using nearest neighbor matching with patients not taking SSRI. The primary endpoint was major bleeding as defined by the International Society on Thrombosis and Haemostasis (ISTH) at 1 year. Kaplan-Meier and Cox regression were used to compare outcomes between treatment groups. Results: Of 1063 patients that underwent PCI during the study period, 1002 met the inclusion criteria and 139 (13.9%) were receiving SSRI. Propensity score distributions, baseline characteristics and standardized mean differences (SMD) of the covariates used for PSM before and after adjustment are shown in Figure 1. In matched survival analysis, there was no significant difference in the primary endpoint at 1 year follow-up: mayor bleeding occurred in 2.9% of patients who received SSRI and in 2.9% of those with no SSRI (HR 1.01; CI 0.25 to 4.03; p=0.991) (Figure 2). Conclusion: In routine clinical care, patients treated with SSRI and DAPT or TAT after PCI did not have a higher risk of bleeding after a year follow-up. FUNDunding Acknowledgement: Type of funding sources: None.